1998
DOI: 10.1037/h0080279
|View full text |Cite
|
Sign up to set email alerts
|

Minority populations in the child welfare system: The visibility hypothesis reexamined.

Abstract: This study tests the "visibility hypothesis," which suggests that there is a higher probability for minority children to be placed in foster care when living in geographic locations where their proportions in the population are relatively low, compared to areas where their proportions are high. Results support the hypothesis for African-American youth only. Explanations of the findings, and their implications for research and practice, are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 7 publications
(19 reference statements)
2
13
0
Order By: Relevance
“…More specifically, their findings revealed that black children were twice as likely to be placed in foster care in counties where they comprised 5-10% of the population than in counties where black children comprised 30-50% of the population. These findings were confirmed two decades later by Garland, MacLeod, Landsverk, and Granger (1998), and Barth, Miller, Green, and Baumgartner (2001). For example, Barth et al, 2001 found that black children who lived in counties where they comprised less than 5% of the population were more likely to be placed in foster care than black children who lived in counties where they comprised more than 15% of the population.…”
Section: Visibility Hypothesissupporting
confidence: 68%
“…More specifically, their findings revealed that black children were twice as likely to be placed in foster care in counties where they comprised 5-10% of the population than in counties where black children comprised 30-50% of the population. These findings were confirmed two decades later by Garland, MacLeod, Landsverk, and Granger (1998), and Barth, Miller, Green, and Baumgartner (2001). For example, Barth et al, 2001 found that black children who lived in counties where they comprised less than 5% of the population were more likely to be placed in foster care than black children who lived in counties where they comprised more than 15% of the population.…”
Section: Visibility Hypothesissupporting
confidence: 68%
“…Although children placed in kinship care or guardianship have many of the same risk factors as children in nonrelative foster care, recent studies have shown that children living with extended family have greater placement stability and that caregivers report fewer behavior and developmental problems compared with children in nonrelative foster care. 2,11,13,14,19 However, the prevalence of behavioral problems for these children is still well above that of community peers, and their caregivers are more likely to be older and poorer and with even less access to services than nonrelative foster caregivers. 2,19,20 Appropriate services and treatment may strengthen the stability of placements, both foster and kinship, and improve child outcomes over the long term.…”
Section: Type Of Placementmentioning
confidence: 99%
“…13 However, concern remains about possible bias in child maltreatment reporting and/or investigation, resulting in the removal of relatively more children of racial or ethnic minority heritage from their families. 14,15 There are a few subgroups of children in foster care deserving of special mention. A small but increasing group of adolescents in foster care are unaccompanied refugee minors, who have entered the United States alone from ravaged homelands, often with no information regarding the fate of their family.…”
Section: Trends In Foster Carementioning
confidence: 99%
“…Minority persons, especially men [Hacker, 1995], with severe mental illness reportedly fall into this category [Garland et al, 1998;Lindsey and Gordon, 1989;Rosenfeld, 1984;Snowden, 1999].…”
Section: Introductionmentioning
confidence: 99%